Psychosocial health stigma related to COVID-19 disease among COVID-19 patients in Jordan: a comparative study - Lina Jalal Daoud; Mamdouh El-hneiti; Mahmoud Ogla Al-Hussami (BMJ Public Health)
Objective Beyond its effects on physical health, COVID-19 psychosocial stigma has emerged as a result of this global crisis, making people feel ashamed, alone and discriminated against. This comparative study aims to assess the psychosocial health stigma of COVID-19, and to evaluate the perceived stigma according to the sociodemographic variables during the pandemic in Jordan.Method A study in Jordan compared stigma between 112 COVID-19 patients (52 males and 60 females) and 118 healthy controls (56 males and 62 females), with participants ranging from 18 to over 60 years old in both groups.Results According to the data, 27% of COVID-19 patients had high-level stigma, with total stigma scores ranging from 46 to 111 and a mean of 80.23 (SD=12.79). Quartile results showed 50% scored 80, 25% over 88 and 75% over 78, indicating moderate stigma within a 0–160 range. On the other hand, the total scores of stigma among the healthy controls ranged from 40 to 112, with a mean of 78.55 (SD=12.41). 30.3% report high levels of stigma. Quartile results showed 50% scored 78, 25% over 85 and 75% over 71, indicating moderate stigma. No significant stigma score difference was found between patients and controls (t=1.09, p=0.28). No significant correlation with demographics, except among medical workers (t=−3.32, p=0.001).Conclusion The study revealed negligible differences in stigma between the two groups, but greater stigma among medical field workers highlighting the need for integrated community and policy support to fight stigma.